Management of Coconut Mite in Bangladesh Involving Communities as Implanter - Islam, Md. Nazirul; Islam, Ishaqul; Shamsunnahar, Mst. (International Coconut Community, 2018)
A study on management of coconut mite (Aceria guerreronis Keifer, Acari: Eriophyidae) was carried out in farmers fields at Bagharpara Sub-district of Jashore district, in an area of about 696 ha during May 2011 to June 2014. The mite attacking coconut in Bangladesh remained unidentified until 2008. Field and laboratory studies on morpho-anatomy revealed that 2-6 month old nuts hosted colonies of mites while no mites were found on unfertilized button (flowers) and nuts of more than 06 months old. Colonization was found maximum in younger nuts of 3 -4 month old. Mites were found to reside under the perianth near the stalk of young coconut. Six different treatments viz, removing of infested young nuts and foliar application of Omite @ 0.2% adjacent to the bunch region (T1); removing of infected young nuts and foliar application of Neem-oil @ 0.3% adjacent to the bunch region (T2); T1 & soil incorporation of Neem cake @ 500g/tree (T3); T1 & soil incorporation of tricho-compost @ 2000g/tree (T4); T2 & soil incorporation of Neem cake @ 500g/tree (T5) and T2 & incorporation of tricho-compost 2000g/tree (T6). Results of three consecutive years showed that all the treatments were equally effective in controlling mite attack in coconut. Edible portion of mature nuts was found to improve by the treatments T3 and T5, containing soil incorporated Neem cake. Days to spath opening, male phase, number of bunch and nut per bunch were not influenced by any one of the treatments. On an average 77 nuts were harvested/palm/year and their estimated market value was Taka 1540. Income augmented due to technology was Taka 1339.80 with BCR value 6.